2022
DOI: 10.1177/14034948221075021
|View full text |Cite
|
Sign up to set email alerts
|

Immigrants’ perspectives on healthy life and healthy lifestyle counseling: a focus group study

Abstract: Background: Immigrants have a higher risk of developing chronic diseases than the general population, but there is a lack of knowledge about appropriate counseling models to promote their health. This study aimed to explore Asian and Russian immigrants’ perspectives in Finland on healthy lifestyle and healthy lifestyle counseling to improve the quality of the counseling in primary health care services to prevent type 2 diabetes and other chronic diseases. Methods: We conducted a qualitative study using semi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…This is in line with a previous Swedish study that has shown that migrants “lack knowledge” about certain health-related issues and also about the health system in Sweden ( 7 ). A study in a Finish setting also showed that migrants experience they have limited knowledge of health-related issues and that this, together with miscommunication, can create problems in the contact between migrants and healthcare personnel ( 6 ). Both knowledge and skills, which were the important aspects of how the civic communicators approached health promotion, are also important aspects in regard to health literacy ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with a previous Swedish study that has shown that migrants “lack knowledge” about certain health-related issues and also about the health system in Sweden ( 7 ). A study in a Finish setting also showed that migrants experience they have limited knowledge of health-related issues and that this, together with miscommunication, can create problems in the contact between migrants and healthcare personnel ( 6 ). Both knowledge and skills, which were the important aspects of how the civic communicators approached health promotion, are also important aspects in regard to health literacy ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Syrians who have resettled in Sweden have a higher prevalence of mental ill health ( 4 ), as well as lower health-related quality of life ( 5 ) than the general population. Research on migrants in Finland shows that they describe having limited knowledge about healthy lifestyles and that they report having received limited information from the healthcare services regarding a healthy lifestyle ( 6 ). In a Swedish context, research has shown that newly arrived migrants have limited health literacy and ask for more information on health-related issues, as well as that the healthcare services sometimes take it for granted that migrants have the same general health knowledge as people who have grown up in Sweden ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, there are many questions as to which components should be included in food supplements. Many researchers have proved that a healthy lifestyle consists of: adherence to an optimal physical activity regime, healthy eating, reducing the harmful effects of stress, giving up bad habits, as well as quality and sufficient sleep, and safe working conditions (Dominguez, et al, 2018;McMaughan, et al, 2020;Nekouei Marvi Langari, et al, 2023).…”
Section: Components Including a Healthy Lifestyle (Hl)mentioning
confidence: 99%
“…Результаты фокус-групп, проведенных в Финляндии с 46 взрослыми мигрантами из России и стран Азии, показали влияние культурных факторов на установки и знания в сфере здоровья, а также значимость разработки программ по пропаганде здорового образа жизни, учитывающих культурную, национальную и языковую специфику [73].…”
Section: The Aim Of This Study Was To Assess Peculiarities Of Bioaccu...unclassified